Analisis Hubungan Suhu, Kelembapan Dan Curah Hujan Di Tana Toraja Dengan Fenomena Perubahan Iklim - Pabontongan, Santonius Sandi; Palloan, Pariabti; Susanto, Agus (Jurnal Fisika Unand, 2024)
The impact of climate change has emerged as a strategic issue threatening the national interests and environment, particularly in the context of Tana Toraja in the tropical region of Indonesia. The process of climate change, influenced by both natural factors and human activities, has led to a global increase in temperatures and climate anomalies. The risks of natural disasters, especially those related to rainfall such as floods, landslides, and the spread of diseases, are on the rise. The Indonesian government needs to design region development strategies with low greenhouse gas emissions and control deforestation. This study employs a qualitative descriptive method and utilizes data from the Pongtiku Toraja Meteorological Station from 2000 to 2019 to analyze the patterns of climate change and the impact of the El-Nino Southern Oscillation (ENSO) in Tana Toraja. The research findings indicate a decrease in the annual average air temperature, an increase in air humidity, and a shift in rainfall patterns towards an equatorial climate type. The impact of ENSO on air temperature, humidity, and rainfall is variable. Predictions suggest a decrease in rainfall, but combined analyses show an average increase of 4.5% per year until 2029. This conclusion provides a holistic overview of climate dynamics in Tana Toraja, crucial for understanding and planning adaptation for the future.